Personal Branding on Social Media Through Peter Montoya Analysis - Samatan, Nuriyati; Adi Prakosa; Robingah Robingah; Napsiah Napsiah (Green Publisher, 2024)
This study aims to analyze the personal branding of Sandra Lubis and Clarissa Putri through social media Instagram @sandradlubis and @clarissaputri_ through Personal Branding Peter Montoya.This research type is Qualitative. This research applied an approach with a constructivism paradigm. The research was conducted with observation, interviews and documentation. Validation is done through data triangulation.The results of the study showed that the personal branding carried out by Sandra Lubis and Clarissa Putri through Instagram @sandradlubis and @clarissaputri_ based on Peter Montoya's personal branding concept, indicated that the branding strategies made by Sandra Lubis and Clarissa Putri, met the standards in Peter Montoya's concept. This leads to, these two endorsers are able to build branding strategies through their respective Instagram. Their reliability in building branding strategies is recognized by their followers through comments on Instagram, and also through expert analysis related to the two influencers who are considered to have a fairly strong branding strategy.